Reconstruction of the clavicle by the induced membrane technique after resection of an aneurysmal bone cyst in children - Mohammed Tazi Charki; Zineb Oudrhiri; Hicham Abdellaoui; karima Atarraf; Moulay Abderrahmane Afifi (Elsevier, 2023)
We report in the case a rare localisation of aneurysmal bone cyst in the internal side of the clavicle in 10 years old girl treated by block-resection and two stage reconstruction of the bone defect by the technique of induced membrane of Masquelet. The clinical and radiological outcomes were good: At 2 years follow-up, the child maintains a normal mobility of shoulder, without complications. In the CT-scan the clavicle was completely reconstructed.Despite the necessity of two surgery stage, the reconstruction of the clavicle with the Masquelet technique is a safe option with good clinical and radiological outcomes.